OC-040 A pre-endoscopy point of care test (iga/igg-deamidated gliadin peptide) as a case finding tool for coeliac diseasein secondary care. (17th June 2017) - Lau, MS; Mooney, PD; White, WL; Rees, MA; Burden, M; Wong, SH; Kurien, M; Sanders, DS
Abstract : Introduction: Coeliac disease (CD) is common yet underdiagnosed. 12.4% CD patients had a gastroscopy within 5 years without duodenal biopsies taken, and coeliac serology was performed in only 30% of patients with anaemia or suspected CD. A pre-endoscopy point of care test (POCT) could potentially fill this gap. We aimed to evaluate the diagnostic accuracy and acceptability of the POCT, Simtomax (IgA/IgG-deamidated gliadin peptide, Tillotts Pharma, Rheinfelden, Switzerland), in detecting CD. Method: Group 1: Patients attending for a gastroscopy were prospectively recruited from 2013–17. We excluded patients with a high pre-test probability of CD: positive endomysial antibody (EMA) referrals, previous villous atrophy, self-reported gluten sensitivity, those on a gluten free diet (GFD), suspected gluten ataxia; and known CD. Group 2: Patients who self-reported gluten sensitivity were prospectively recruited. All patients underwent the POCT, tissue transglutaminase antibodies (TTG), EMA and duodenal biopsies. The sensitivities of the POCT were compared to TTG and EMA, measuring against histology as the reference standard. Questionnaires regarding patient preference to the modality of antibody testing were given out. Results: Group 1: 1000 patients were recruited (585 females, 58.5%; age range 16–91, median age 57). Forty-one patients (4.1%) were diagnosed with CD. Group 1: Group 2: Seventy patients who self-reported gluten sensitivity were recruited (51 females, 82.9%; age range 17–73, median age 35). Nine patients on a self-imposed GFD were excluded. Of the remaining 61 patients, 42 (68.9%) were diagnosed with non-coeliac gluten sensitivity (NCGS), 17 (27.9%) with CD and 2 (3.3%) with potential CD. Group 2: Five hundred patients responded to the POCT acceptability questionnaire. 90.8% preferred a POCT, 2.8% preferred venepuncture, and 6.8% had no preference. Conclusion: The POCT had comparable diagnostic performance to conventional serology. It also correctly identified all cases of CD in a gluten sensitive cohort. The POCT could serve as a valuable and convenient case finding tool, with the advantage of providing antibody results rapidly at the point of endoscopy to target duodenal biopsy sampling for those with a positive POCT. Disclosure of Interest: M. Lau: None Declared, P. Mooney: None Declared, W. White: None Declared, M. Rees: None Declared, M. Burden: None Declared, S. Wong: None Declared, M. Kurien: None Declared, D. Sanders Conflict with: Professor Sanders has received educational research grants from Dr Schaer (a gluten-free food manufacturer) and Tillotts Pharma (producer of a point of care test for celiac disease) for investigator led studies. Dr Shaer and Tillott's Pharma did not have any input in the study design, access to study data, interpretation of the findings or drafting of the manuscript.